Hubungan Interaksi Obat Antidiabetik Dengan Luaran Klinik Pada Pasien DM Tipe 2 Rawat Inap di RS PKU Muhammadiyah Gamping Yogyakarta - Sugiyono, Sugiyono; Padmasari, Siwi; Al Madury, Shalahuddin (MEDIA ILMU KESEHATAN, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a chronic disease that often requires combination therapy, increasing the risk of drug interactions due to polypharmacy, which can affect clinical outcomes. Objective: To examine the relationship between the potential for drug interactions and clinical outcomes in hospitalized T2DM patients at PKU Muhammadiyah Gamping Hospital, Yogyakarta, from January 2022 to August 2023. Methods: This study employed a non-experimental analytical method with a retrospective approach, involving 179 patients who met the inclusion criteria. Univariate analysis was used to describe patient characteristics, medication patterns, and Random Blood Glucose (RBG) levels, while bivariate analysis (Chi-Square test) assessed the relationship between the potential for drug interactions and clinical outcomes.Results: The majority of T2DM patients were aged 41-59 years (50.28%), female (54.75%), and had comorbidities (91.62%). The most common treatment regimen was monotherapy with metformin (46.37%). Most patients received ≥5 medications (88.27%), and 81.56% had potential drug interactions. The predominant interaction mechanism was pharmacodynamic (86.21%) with moderate severity (89.72%). Chi-Square analysis yielded a p-value of 0.082 (p>0.05).Conclusion: No significant relationship was found between the potential for antidiabetic drug interactions and clinical outcomes in patients